Association Between Wait Time for Transcatheter Aortic Valve Replacement and Early Postprocedural Outcomes. Issue 1 (8th January 2019) - Elbaz‐Greener, Gabby; Yarranton, Brianne; Qiu, Feng; Wood, David A.; Webb, John G.; Fremes, Stephen E.; Radhakrishnan, Sam; Wijeysundera, Harindra C.
Abstract : Background: Rapid growth in transcatheter aortic valve replacement (TAVR) demand has translated to inadequate access, reflected by prolonged wait times. Increasing wait times are associated with important adverse outcomes while on the wait‐list; however, it is unknown if prolonged wait times influence postprocedural outcomes. Our objective was to determine the association between TAVR wait times and postprocedural outcomes. Methods and Results: In this population‐based study in Ontario, Canada, we identified all TAVR procedures between April 1, 2010, and March 31, 2016. Wait time was defined as the number of days between initial referral and the procedure. Primary outcomes of interest were 30‐day all‐cause mortality and all‐cause readmission. Multivariable regression models incorporated wait time as a nonlinear variable, using cubic splines. The study cohort included 2170 TAVR procedures, of which 1741 cases were elective and 429 were urgent. There was a significant, nonlinear relationship between TAVR wait time and post‐TAVR 30‐day mortality, as well as 30‐day readmission. We observed an increased hazard associated with shorter wait times that diminished as wait times increased. This statistically significant nonlinear relationship was seen in the unadjusted model as well as after adjusting for clinical variables. However, after adjusting for case urgency status, there was no relationship between wait times and postprocedural outcomes. In sensitivity analyses restricted to either only elective or only urgent cases, there was no relationship between wait times and postprocedural outcomes. Conclusions: Wait time has a complex relationship with postprocedural outcomes that is mediated entirely by urgency status. This suggests that further research should elucidate factors that predict hospitalization requiring urgent TAVR while on the wait list.